2021
DOI: 10.1111/hsc.13685
|View full text |Cite
|
Sign up to set email alerts
|

Person‐ and family‐centred goal‐setting for older adults in Canadian home care: A solution‐focused approach

Abstract: With growing evidence supporting person-and family-centred care (PFCC), there is increasing demand for healthcare providers to partner directly with patients and caregivers in care planning and delivery (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“… 16 , 30 , 56 However, research in other countries (eg Scandinavia, Ireland, Canada) presents family members differently. Here the family is typically presented as a resource for reablement staff to draw on and work with, 27 , 29 or family resistance is downplayed or presented as a minor issue. 26 , 78 For example, a recent Norwegian study reported that adult children encourage their parents to receive reablement services, feel responsible for service delivery, and have a strong will to initiate cooperation with services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 , 30 , 56 However, research in other countries (eg Scandinavia, Ireland, Canada) presents family members differently. Here the family is typically presented as a resource for reablement staff to draw on and work with, 27 , 29 or family resistance is downplayed or presented as a minor issue. 26 , 78 For example, a recent Norwegian study reported that adult children encourage their parents to receive reablement services, feel responsible for service delivery, and have a strong will to initiate cooperation with services.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 16 , 24 , 54–56 The need for effective information and communication strategies has therefore been highlighted both by research and implementation guidance. 8 , 22 , 25 , 27 , 29 , 30 , 55 , 57 , 58 However, less is understood about what those information and communication strategies need to look like.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goal setting for older individuals can be quite challenging; in the home health environment this process is often hindered by a lack of structure in personal and family-based care planning, inconsistent decision making involving various family members, and the difficulties of coordinating multiple task-oriented health care delivery models. 24 Success for the home health care professional in this domain likely depends on early identification of the key decision makers within the care recipient’s family structure (however far-flung it may be) and folding their respective input into the short term and long term goals which comprise the individual’s plan of care. Such early identification and integration into the plan of care conceivably may help greatly to reduce the emotional and physical toll experienced by the informal caregiver or caregivers who provide the majority of assistance on a day-to-day basis for the care recipient.…”
Section: Begin With the End In Mind: Evidence-based Strategies For Re...mentioning
confidence: 99%
“…Ageist assumptions likely influence gerontological health care workers’ perceptions of personal goal setting in older people in that they may falsely believe that they are not intent on pursuing goals beyond those related to functional abilities (e.g., improved mobility) [ 1 ]. However, “new paradigms are needed to provide guidance and support as adults move into the later decades of life, strive to maintain their independence, intent upon aging in place” [ 2 , p.205].…”
Section: Introductionmentioning
confidence: 99%